PENGARUH KECEMASAN BELAJAR MATEMATIS TERHADAP KEMAMPUAN MENYELESAIKAN SOAL MATEMATIKA SISWA KELAS 5 SDN SETIA ASIH - Sari, Adi Dwi Yesika Permata; Mujazi (IPI Press, 2024)
This study aims to analyze the influence of mathematical learning anxiety on the problem-solving ability of fifth-grade students at SDN Setia Asih 01. This research employs a quantitative approach using a survey method. The population consists of all fifth-grade students at SDN Setia Asih 01, totaling 44 students, while the sample includes 25 students from class V A, selected using purposive sampling techniques. Data were collected through questionnaires and math problems. The results of the analysis show that the t-test produces an α value of 0.00<0.05, with t-statistic -11.991, which is smaller than the t-table value of 2.069, indicating that H0 is accepted and H1 is rejected. This implies that mathematical learning anxiety negatively affects problem-solving ability. The coefficient of determination (R Square) value of 0.862 indicates that mathematical learning anxiety influences problem-solving ability by 86.2%, while the remaining 13.8% is influenced by other factors not examined in this study.